Stress Affects The Performance of Nurses During The Covid-19 Pandemic - Widyayantiningsih, Sri; Suci, Lukyta; Feriani, Nita; Muklis, Miatul; Dwi, Yeti; Susandiatman, Anis (Health Gate, 2023)
Various psychological disorders have been reported and publishedduring the Covid-19 outbreak, one of which is stress. Nurse stress can interfere with nurse performance if it is not quickly resolved. The purpose of this study was to analyze the relationship between nurse work stress andnurse performance during the Covid-19 pandemic. This research is an analytic observational study with a cross sectional approach. The population in this study were 46 nurses in the inpatient room of Mas Mansur Building and the Emergency Room of RSU Aminah Blitar. The entire population is used as a sample, namely as many as 46 nurses. Nurse workstress was measured using a questionnaire from DASS-21 (Depression Anxiety Stress Scales_21) and nurse performance was measured using a questionnaire that had been preparedby the researcher.ρ = 0.000). It was concluded that the higher the work stress felt by the nurse, the lower the nurse's performance.